2023
DOI: 10.3390/biom13030466
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Antibacterial Peptide, PAM-5, via Combination of Phage Display Selection and Computer-Assisted Modification

Abstract: Antibacterial peptides (ABPs) have been proposed as potential candidates for alternative antibacterial agents due to the extensive dissemination of antibiotic resistance. However, ABP isolation from natural resources can be tedious without consistent yield. Moreover, many natural ABPs are not developed for clinical application due to potential toxicity to mammalian cells. Therefore, the objective of this study was to develop a potent ABP with minimal toxicity via phage display selection followed by computer-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The results showed that the MIC ranged from 0.98 to 500 μM, while the MBC ranged from 4 to 650 μM, indicating a bactericidal effect. Yuen et al 237 combined phage display technology with computer‐assisted modifications and developed a novel antimicrobial peptide called PAM‐5. This peptide exerts antimicrobial activity by disrupting bacterial membranes and interacting with bacterial DNA.…”
Section: Biomedical Applications Of Peptides and Pasmentioning
confidence: 99%
“…The results showed that the MIC ranged from 0.98 to 500 μM, while the MBC ranged from 4 to 650 μM, indicating a bactericidal effect. Yuen et al 237 combined phage display technology with computer‐assisted modifications and developed a novel antimicrobial peptide called PAM‐5. This peptide exerts antimicrobial activity by disrupting bacterial membranes and interacting with bacterial DNA.…”
Section: Biomedical Applications Of Peptides and Pasmentioning
confidence: 99%
“…The dye SYTOX Green (a DNA intercalator) was used for this test, as performed by Yuen et al [65]. Initially, the inocula of S. aureus 1199B and K2068 were distributed in the 96-well black plate, and then, we added C1 coumarin until final concentrations of 200 µg/mL, 100 µg/mL, 50 µg/mL, and 25 µg/mL were obtained.…”
Section: Effects On Membrane Permeabilitymentioning
confidence: 99%